Literacy of Sexual Harassment and Abuse Toward Adolescent Protection Behavior - Ananda Dwitha Yuniar; Ananda Nur Azahra; Adenia Qonitalillah; Anggaunitakiranantika (Muwazah, 2022)
Cases of harassment in Indonesia are increasingly starting with victims voicing on social media regarding what happened to them. KOMNAS Perempuan noted that the spectrum of sexual harassment and violence against women has increased to reach 792% to 800%. This seems to be an alarm for all of us to have the knowledge of self-protection to avoid sexual harassment and violence. This study aims to measure the extent of literacy of sexual harassment and violence on the level of self-protection in Malang. It is known that the quantitative research method uses a questionnaire questionnaire with several question items from the X variable and Y variable, the questionnaire is distributed to students throughout the city of Malang and the results show that there is a relationship between literacy regarding sexual harassment and violence with the level of self-protection in individuals. . From the results of the study, it was found that most of the respondents had high scores in literacy about sexual harassment and violence, regarding this literacy they knew at least basic knowledge about violence and sexual harassment and were able to increase self-protection anywhere with literacy.